A polymer fluid loss reducer for drilling fluid and preparation method thereof
By using polymer filter loss agents in drilling fluids, a hydrogel coating with high crosslinking degree is formed by polymerization and crosslinking through ultraviolet light irradiation, and combined with lignin hybrids to form a multi-layer structure, the existing filter loss agents have been solved in terms of stability, high temperature resistance and filter loss performance, and the efficient filter loss reduction effect is achieved.
Patent Information
- Application Number
- CN202411686946.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-11-25
AI Technical Summary
The existing filtration reduction agents for drilling fluids have poor comprehensive performance in terms of stability, high temperature resistance and filtration reduction performance, making it difficult to meet the needs of complex formations in deep well drilling.
Using a preparation method of polymer filter loss reduction agent, DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid are polymerized and cross-linked at a specific molar ratio to form an A-PDMA hydrogel coating with high cross-linking degree, and combined with B-PDMA-lignin hybrids to form a multi-layer structure to improve the filter loss reduction effect.
The high stability, high temperature resistance and strong filtration loss reduction effect of the filter reduction agent for drilling fluid are achieved, which can significantly reduce the filtration loss in a high-temperature and high-pressure environment and improve the quality of the drilling fluid.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of oil drilling fluid loss reduction, and more specifically, relates to a polymer fluid loss reducer for drilling fluid and a preparation method thereof. Background Art
[0002] Considering that complex formations are frequently encountered during deep well drilling, it is urgent to develop a fluid loss reducer that can reduce fluid loss and withstand high temperatures. At present, fluid loss reducers are mainly divided into the following categories: polymer fluid loss reducers that can withstand temperatures of about 150°C, but are easily degraded at high temperatures; zwitterionic polymers that can withstand temperatures of about 160°C, but have poor salt resistance and fluid loss reduction effects; cellulose fluid loss reducers that can withstand temperatures of about 120°C, but have poor high temperature resistance.
[0003] Therefore, in the drilling environment, a fluid loss reducer with the function of plugging and reducing fluid loss and improving the quality of mud cake is particularly important. At present, it is urgent to prepare a fluid loss reducer for drilling fluid with strong stability, high temperature resistance and strong fluid loss reduction performance. Summary of the invention
[0004] 1. Problem to be solved
[0005] Aiming at the problem that the prior art drilling fluid fluid loss reducer has poor comprehensive performance such as stability, high temperature resistance and fluid loss reduction performance, the present invention provides a polymer fluid loss reducer for drilling fluid and a preparation method thereof.
[0006] 2. Technical solution
[0007] In order to solve the above problems, the technical solution adopted by the present invention is as follows:
[0008] A method for preparing a polymer fluid loss reducer for drilling fluid of the present invention comprises the following steps:
[0009] (1) N,N-dimethylacrylamide (DMA in the following text), N,N-methylenebisacrylamide and α-ketoglutaric acid were mixed in water at a molar ratio of 1:(0.005-0.015):(0.001-0.005) and then injected into a 100×100×2 mm 3 And in a rectangular mold that can transmit ultraviolet light;
[0010] (2) A rectangular mold containing an aqueous solution of DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid was exposed to 200-300 W ultraviolet light for 8-16 hours, wherein the ultraviolet light was directly irradiated on a 100×100 mm area of the rectangular mold. 2 On the other hand, after the reaction is completed, the solid A-type PDMA, i.e. A-PDMA, is obtained by drying;
[0011] In the above steps, DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid were prepared in a 100 × 100 × 2 mm 3 The rectangular mold was irradiated with ultraviolet light to initiate polymerization and cross-linking reactions, and the molar ratio was controlled to be 1: (0.005-0.015): (0.001-0.005) and the 100×100 mm rectangular mold was irradiated with ultraviolet light. 2 One side can be fully cross-linked under the premise of ensuring a certain degree of polymerization of the product PDMA to form A-PDMA with moderate molecular weight and high cross-linking degree. After this A-PDMA is used to form a fluid loss reducer, as the solvent (water or DMF) naturally evaporates, A-PDMA will self-assemble with the B-PDMA-lignin hybrid in the subsequent steps, and form an A-PDMA hydrogel coating with a stable structure floating on the surface through a swelling process, thereby effectively reducing fluid loss.
[0012] (3) adding DMA, N,N-methylenebisacrylamide, initiator and lignin into a solvent DMF and mixing and reacting them at 40-60°C for 14-20 hours to obtain a hybrid solution of type B PDMA and lignin, i.e., a B-PDMA-lignin hybrid solution; wherein the molar ratio of DMA, N,N-methylenebisacrylamide and initiator is 1:(0.001-0.005):(0.0005-0.004), and the mass ratio of DMA to lignin is 1:(0.5-4);
[0013] In the above steps, DMA, N,N-methylenebisacrylamide and initiator in a molar ratio of 1: (0.001-0.005): (0.0005-0.004) undergo polymerization reaction and hybridization process with lignin at 40-60°C. At the same time, a suitable molar ratio will form B-PDMA with a high molecular weight and a moderate degree of crosslinking. After the B-PDMA with such characteristics is used to form a fluid loss reducer, as the solvent (water or DMF) naturally evaporates, the B-PDMA-lignin hybrid will self-assemble with the A-PDMA in the above step (2), and the B-PDMA will be highly soluble in water and lignin through the swelling process. The sub-hydrogel coating is located between the A-PDMA hydrogel coating and the lignin layer to tightly couple the two, while the bottom lignin aggregation layer forms a strong interface adhesion with the micropore interface in the drilling environment by virtue of dense van der Waals forces, thus forming a highly stable multi-layer structure of top A-PDMA hydrogel coating + middle B-PDMA polymer hydrogel coating + bottom lignin layer. The hydrophobic lignin aggregation area at the bottom not only makes the upper and middle layers of the hydrogel coating have high strength and toughness, but also limits the swelling of the hydrogel coating in water, thereby forming a dense ultra-thin hydrogel coating covering the surface, achieving a highly stable filtration loss reduction effect.
[0014] (4) Add the A-PDMA to the B-PDMA-lignin hybrid solution, mix and stir evenly, and incubate at room temperature for 12 to 36 hours to obtain a mixed gel of A-PDMA / B-PDMA-lignin, which is a fluid loss reducer.
[0015] In the above steps, static incubation at room temperature can effectively hybridize A-PDMA and B-PDMA-lignin hybrids, and the formed fluid loss reducer self-assembles into a multi-layer structure with high strength, toughness and stability during the solvent volatilization process, and its fluid loss reduction performance is relatively high. The specific principle is as described above.
[0016] Furthermore, the rectangular mold is made of glass with an ultraviolet transmittance of ≥90%.
[0017] Furthermore, in the step (1), 20 mL of a DMA aqueous solution with a concentration of 1-10 wt.% is prepared, N,N-methylenebisacrylamide and α-ketoglutaric acid are added to the DMA aqueous solution and stirred evenly, and then the stirred mixed aqueous solution is injected into the rectangular mold.
[0018] Furthermore, the molar ratio of DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid is 1:0.012:0.004.
[0019] Furthermore, in the step (2), the wavelength of the ultraviolet light is 360-380 nm.
[0020] Furthermore, in the step (2), the product after the reaction is dried at 30-40° C. to obtain the A-PDMA.
[0021] Furthermore, in the step (3), lignin is first added to 30 mL of solvent DMF and stirred until completely dissolved to obtain a DMF solution of lignin with a concentration of 1 to 10 wt.%, and then DMA, N,N-methylenebisacrylamide and an initiator are added to the DMF solution of lignin to react.
[0022] Furthermore, the initiator includes one or more of azobisisobutyronitrile, azobiscyclohexanecarbonitrile, and benzoyl peroxide.
[0023] Furthermore, in the step (4), the mass ratio of the A-PDMA to the B-PDMA in the B-PDMA-lignin hybrid is 1:(1.2-2.5).
[0024] The present invention also protects a polymer fluid loss reducer for drilling fluid, which is prepared by any one of the preparation methods described above.
[0025] 3. Beneficial effects
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) A method for preparing a polymer fluid loss reducer for drilling fluid of the present invention. After the prepared fluid loss reducer for drilling fluid is filled into the base slurry, as the solvent (water or DMF) evaporates, the B-PDMA-lignin hybrid will self-assemble with the A-PDMA. Through the swelling process, the B-PDMA polymer hydrogel coating is interposed between the A-PDMA hydrogel coating and the lignin layer, tightly coupling the two. The A-PDMA hydrogel coating with a moderate molecular weight, high crosslinking degree and high stability will float on the surface, and the bottom lignin aggregation layer will be densely connected to the bottom lignin layer. The van der Waals force forms a strong interfacial adhesion with the micropore interface in the drilling environment, thus forming a highly stable multi-layer structure of top A-PDMA hydrogel coating + middle B-PDMA polymer hydrogel coating + bottom lignin layer. The hydrophobic lignin aggregation area at the bottom makes the upper and middle hydrogel coatings have high strength and toughness on the one hand, and limits the swelling of the hydrogel coating in water on the other hand, thereby forming a dense ultra-thin hydrogel coating covering the surface and filling the micropores, achieving a highly stable filtration loss reduction effect, and still having a low filtration loss under high temperature and high pressure environment.
[0028] (2) A polymer fluid loss reducer for drilling fluid of the present invention is obtained by the preparation method of the present invention and has all the beneficial effects of the preparation method of the present invention. DETAILED DESCRIPTION
[0029] The more detailed description of the embodiments of the present invention below is not intended to limit the scope of the claimed invention, but is merely for illustration and not to limit the description of the features and characteristics of the present invention, so as to propose the best mode for performing the present invention, and to be sufficient to enable those skilled in the art to implement the present invention. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and if there are any such modifications and variations, they will all fall within the scope of the present invention described herein. In addition, the background technology is intended to illustrate the current status and significance of the research and development of the present technology, and is not intended to limit the present invention or the application field of the present application and the present invention.
[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the present invention belongs; the terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0031] The present invention is further described below in conjunction with specific embodiments. Example 1
[0032] This embodiment provides a polymer fluid loss reducer for drilling fluid, and the preparation method thereof specifically comprises the following steps:
[0033] (1) Prepare 20 mL of 5 wt.% DMA aqueous solution, add N,N-methylenebisacrylamide and α-ketoglutaric acid to the DMA aqueous solution and stir evenly. Then inject the mixed aqueous solution into a 100×100×2 mm 3 and a rectangular mold that can transmit ultraviolet light; wherein DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid are mixed uniformly in water at a molar ratio of 1:0.012:0.004 and then injected, and the rectangular mold is made of glass with an ultraviolet transmittance of ≥90%;
[0034] (2) A rectangular mold containing an aqueous solution of DMA, N,N-methylenebisacrylamide, and α-ketoglutaric acid was exposed to 260 W ultraviolet light for 12 hours, wherein the ultraviolet light was directly irradiated on a 100 × 100 mm rectangular mold. 2 On one side, the product after the reaction is dried at 35°C to obtain solid type A PDMA, i.e. A-PDMA; wherein the wavelength of the ultraviolet light is 360-380nm;
[0035] (3) First, lignin was added to 30 mL of solvent DMF and stirred until completely dissolved to obtain a DMF solution of lignin with a concentration of 5 wt.%, and then DMA, N,N-methylenebisacrylamide, and initiator azobiscyclohexanecarbonitrile were added to the DMF solution of lignin and mixed for reaction at 45°C for 18 hours to obtain a hybrid solution of type B PDMA and lignin, i.e., B-PDMA-lignin hybrid solution; wherein the molar ratio of DMA, N,N-methylenebisacrylamide and azobiscyclohexanecarbonitrile was 1:0.003:0.001, and the mass ratio of DMA to lignin was 1:2.5;
[0036] (4) Add the A-PDMA to the B-PDMA-lignin hybrid solution and mix and stir evenly, wherein the mass ratio of A-PDMA to B-PDMA in the B-PDMA-lignin hybrid is 1:1.4, and incubate at room temperature for 20 hours to obtain a mixed gel of A-PDMA / B-PDMA-lignin, which is a filtrate reducer.
[0037] The fluid loss reducer prepared in this example was used to prepare drilling fluid: ① Fresh water base slurry: add 2.75g of anhydrous sodium carbonate and 60g of bentonite to every 1000mL of water, stir at high speed for 20min, and cure at room temperature for 24h to obtain base slurry. ② 15% salt water base slurry: add 15wt.% sodium chloride to the fresh water base slurry.
[0038] In order to facilitate the configuration of the drilling fluid system for testing, the mixed gel of A-PDMA / B-PDMA-lignin prepared in this example was concentrated to a fluid loss reducer with a solute concentration of 40 wt.%. The fluid loss reducer was placed in 500 mL of the prepared fresh water base slurry and 15% salt water base slurry, respectively, and high-speed sheared for 15 minutes to obtain a drilling fluid system; wherein the weight of the solute in the fluid loss reducer was 5% of the weight of the fresh water base slurry or the 15% salt water base slurry, and then the performance of the drilling fluid was measured.
[0039] The specific test process of the high temperature resistance performance test of the drilling fluid is: high temperature and high pressure filtration test and high temperature hot rolling aging test, which are carried out in accordance with the national standard GB / T16783.1-2014 test method. The high temperature hot rolling aging test process is: hot rolling 240℃ / 16h aging, then take out, and after the drilling fluid is stirred at high speed for 10min, the relevant performance is tested at room temperature. The test results are shown in Table 1.
[0040] Table 1. Comparison of performance of fluid loss reducers obtained in various implementation methods
[0041] Example 2
[0042] This embodiment provides a polymer fluid loss reducer for drilling fluid, and the preparation method thereof specifically comprises the following steps:
[0043] (1) Prepare 20 mL of 6 wt.% DMA aqueous solution, add N,N-methylenebisacrylamide and α-ketoglutaric acid to the DMA aqueous solution and stir evenly. Then inject the mixed aqueous solution into a 100×100×2 mm 3 and a rectangular mold that can transmit ultraviolet light; wherein DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid are mixed uniformly in water at a molar ratio of 1:0.007:0.001 and then injected, and the rectangular mold is made of glass with an ultraviolet transmittance of ≥90%;
[0044] (2) A rectangular mold containing an aqueous solution of DMA, N,N-methylenebisacrylamide, and α-ketoglutaric acid was exposed to 260 W ultraviolet light for 8 hours, wherein the ultraviolet light was directly irradiated on a 100×100 mm area of the rectangular mold. 2 On one side, the product after the reaction is dried at 30°C to obtain solid type A PDMA, i.e. A-PDMA; wherein the wavelength of the ultraviolet light is 360-380nm;
[0045] (3) First, lignin was added to 30 mL of solvent DMF and stirred until completely dissolved to obtain a DMF solution of lignin with a concentration of 6 wt.%, and then DMA, N,N-methylenebisacrylamide, and initiator azobisisobutyronitrile were added to the DMF solution of lignin and mixed and reacted at 50°C for 20 hours to obtain a hybrid solution of type B PDMA and lignin, namely, B-PDMA-lignin hybrid solution; wherein the molar ratio of DMA, N,N-methylenebisacrylamide and azobisisobutyronitrile was 1:0.002:0.002, and the mass ratio of DMA to lignin was 1:2;
[0046] (4) Add the A-PDMA to the B-PDMA-lignin hybrid solution and mix and stir evenly, wherein the mass ratio of A-PDMA to B-PDMA in the B-PDMA-lignin hybrid is 1:1.2, and incubate at room temperature for 24 hours to obtain a mixed gel of A-PDMA / B-PDMA-lignin, which is a filtrate reducer.
[0047] The fluid loss reducer prepared in this example was used to prepare drilling fluid: ① Fresh water base slurry: add 2.75g of anhydrous sodium carbonate and 60g of bentonite to every 1000mL of water, stir at high speed for 20min, and cure at room temperature for 24h to obtain base slurry. ② 15% salt water base slurry: add 15wt.% sodium chloride to the fresh water base slurry.
[0048] In order to facilitate the configuration of the drilling fluid system for testing, the mixed gel of A-PDMA / B-PDMA-lignin prepared in this example was concentrated to a fluid loss reducer with a solute concentration of 40 wt.%. The fluid loss reducer was placed in 500 mL of the prepared fresh water base slurry and 15% salt water base slurry, respectively, and high-speed sheared for 15 minutes to obtain a drilling fluid system; wherein the weight of the solute in the fluid loss reducer was 5% of the weight of the fresh water base slurry or the 15% salt water base slurry, and then the performance of the drilling fluid was measured.
[0049] The specific test process of the high temperature resistance performance test of the drilling fluid is: high temperature and high pressure filtration test and high temperature hot rolling aging test, which are carried out in accordance with the national standard GB / T16783.1-2014 test method. The high temperature hot rolling aging test process is: hot rolling 240℃ / 16h aging, then take out, and after the drilling fluid is stirred at high speed for 10min, the relevant performance is tested at room temperature. The test results are shown in Table 1. Example 3
[0050] This embodiment provides a polymer fluid loss reducer for drilling fluid, and the preparation method thereof specifically comprises the following steps:
[0051] (1) Prepare 20 mL of 3 wt.% DMA aqueous solution, add N,N-methylenebisacrylamide and α-ketoglutaric acid to the DMA aqueous solution and stir evenly. Then inject the mixed aqueous solution into a 100×100×2 mm 3 and a rectangular mold that can transmit ultraviolet light; wherein DMA, N,N-methylenebisacrylamide and α-ketoglutaric acid are mixed uniformly in water at a molar ratio of 1:0.015:0.005 and then injected, and the rectangular mold is made of glass with an ultraviolet transmittance of ≥90%;
[0052] (2) A rectangular mold containing an aqueous solution of DMA, N,N-methylenebisacrylamide, and α-ketoglutaric acid was exposed to 260 W ultraviolet light for 16 hours, wherein the ultraviolet light was directly irradiated on a 100 × 100 mm rectangular mold. 2 On one side, the product after the reaction is dried at 40°C to obtain solid type A PDMA, i.e. A-PDMA; wherein the wavelength of the ultraviolet light is 360-380nm;
[0053] (3) First, lignin was added to 30 mL of solvent DMF and stirred until completely dissolved to obtain a DMF solution of lignin with a concentration of 3 wt.%, and then DMA, N,N-methylenebisacrylamide, and initiator benzoyl peroxide were added to the DMF solution of lignin and mixed and reacted at 60°C for 20 hours to obtain a hybrid solution of type B PDMA and lignin, namely, B-PDMA-lignin hybrid solution; wherein the molar ratio of DMA, N,N-methylenebisacrylamide and benzoyl peroxide was 1:0.005:0.003, and the mass ratio of DMA to lignin was 1:4;
[0054] (4) Add the A-PDMA to the B-PDMA-lignin hybrid solution and mix and stir evenly, wherein the mass ratio of A-PDMA to B-PDMA in the B-PDMA-lignin hybrid is 1:2, and incubate at room temperature for 24 hours to obtain a mixed gel of A-PDMA / B-PDMA-lignin, which is a filtrate reducer.
[0055] The fluid loss reducer prepared in this example was used to prepare drilling fluid: ① Fresh water base slurry: add 2.75g of anhydrous sodium carbonate and 60g of bentonite to every 1000mL of water, stir at high speed for 20min, and cure at room temperature for 24h to obtain base slurry. ② 15% salt water base slurry: add 15wt.% sodium chloride to the fresh water base slurry.
[0056] In order to facilitate the configuration of the drilling fluid system for testing, the mixed gel of A-PDMA / B-PDMA-lignin prepared in this example was concentrated to a fluid loss reducer with a solute concentration of 40 wt.%. The fluid loss reducer was placed in 500 mL of the prepared fresh water base slurry and 15% salt water base slurry, respectively, and high-speed sheared for 15 minutes to obtain a drilling fluid system; wherein the weight of the solute in the fluid loss reducer was 5% of the weight of the fresh water base slurry or the 15% salt water base slurry, and then the performance of the drilling fluid was measured.
[0057] The specific test process of the high temperature resistance performance test of the drilling fluid is: high temperature and high pressure filtration test and high temperature hot rolling aging test, which are carried out in accordance with the national standard GB / T16783.1-2014 test method. The high temperature hot rolling aging test process is: hot rolling 240℃ / 16h aging, then take out, and after the drilling fluid is stirred at high speed for 10min, the relevant performance is tested at room temperature. The test results are shown in Table 1.
[0058] Comparative Example 1
[0059] The drilling fluid of this comparative example was tested directly after being prepared: ① Fresh water base slurry: add 2.75g of anhydrous sodium carbonate and 60g of bentonite to every 1000mL of water, stir at high speed for 20min, and cure at room temperature for 24h to obtain base slurry. ② 15% salt water base slurry: add 15wt.% sodium chloride to the fresh water base slurry.
[0060] The specific test process of the high temperature resistance performance test of the drilling fluid is: high temperature and high pressure filtration test and high temperature hot rolling aging test, which are carried out in accordance with the national standard GB / T16783.1-2014 test method. The high temperature hot rolling aging test process is: hot rolling 240℃ / 16h aging, then take out, and after the drilling fluid is stirred at high speed for 10min, the relevant performance is tested at room temperature. The test results are shown in Table 1.
[0061] The difference between the drilling fluid system of this comparative example 1 and the embodiment is that the fluid loss reducer of the present application is not added.
[0062] Comparative Example 2
[0063] This comparative example provides a polymer fluid loss reducer for drilling fluid, and its preparation method specifically comprises the following steps:
[0064] First, lignin is added into 30 mL of solvent DMF and stirred until completely dissolved to obtain a DMF solution of lignin with a concentration of 5 wt.%, and then DMA, N, N-methylenebisacrylamide, and initiator azobiscyclohexanecarbonitrile are added into the DMF solution of lignin and mixed and reacted at 45° C. for 18 hours to obtain a hybrid solution of type B PDMA and lignin, i.e., a B-PDMA-lignin hybrid solution, which is a fluid loss reducer; wherein the molar ratio of DMA, N, N-methylenebisacrylamide and azobiscyclohexanecarbonitrile is 1:0.003:0.001, and the mass ratio of DMA to lignin is 1:2.5.
[0065] The main difference between the drilling fluid fluid loss reducer of this comparative example 2 and that of Example 1 is that the B-PDMA-lignin hybrid solution is directly used as the fluid loss reducer, eliminating the preparation of A-PDMA and the subsequent preparation of the mixed gel of A-PDMA / B-PDMA-lignin.
[0066] Drilling fluid was prepared for the fluid loss reducer prepared in this comparative example: ① Fresh water base slurry: add 2.75g of anhydrous sodium carbonate and 60g of bentonite to every 1000mL of water, stir at high speed for 20min, and cure at room temperature for 24h to obtain base slurry. ② 15% salt water base slurry: add 15wt.% sodium chloride to the fresh water base slurry.
[0067] In order to facilitate the preparation of the drilling fluid system for testing, the B-PDMA-lignin solution prepared in this comparative example was concentrated to a fluid loss reducer with a solute concentration of 40wt.%. The fluid loss reducer was placed in 500mL of the prepared fresh water base slurry and 15% salt water base slurry, respectively, and high-speed sheared for 15min to obtain a drilling fluid system; wherein the weight of the solute in the fluid loss reducer was 5% of the weight of the fresh water base slurry or the 15% salt water base slurry, and then the performance of the drilling fluid was measured.
[0068] The specific test process of the high temperature resistance performance test of the drilling fluid is: high temperature and high pressure filtration test and high temperature hot rolling aging test, which are carried out in accordance with the national standard GB / T16783.1-2014 test method. The high temperature hot rolling aging test process is: hot rolling 240℃ / 16h aging, then take out, and after the drilling fluid is stirred at high speed for 10min, the relevant performance is tested at room temperature. The test results are shown in Table 1.
[0069] By comparing Examples 1 to 3 and Comparative Examples 1 to 2, it can be seen that the filtration reducer prepared in the embodiments of the present application effectively reduces the high-temperature and high-pressure filtration loss in the drilling environment, and can also maintain a low filtration loss of about 5 mL in a high-salt environment. In addition, the filtration reducer after hot rolling aging at 240°C / 16h can still keep the high-temperature and high-pressure filtration loss below 9 mL. This is largely due to the fact that the filtration reducer of the present application swells to form a stable structure of a multi-layer after the solvent evaporates in the drilling environment. The dense lignin area at the bottom of the structure can effectively combine closely with the micropore interface, and the ultra-thin hydrogel coating with high cross-linking degree and high stability at the top effectively hinders the filtration loss of the drilling fluid, thereby improving the filtration loss reduction performance under high temperature and high pressure environments. Among them, the filtration loss of Comparative Example 1 without adding the filtration reducer of the present application increased significantly, and although Comparative Example 2 has a certain filtration loss reduction performance, it is likely that it is because the ultra-thin hydrogel coating A-PDMA with high cross-linking degree and high stability at the top is coupled with the bottom B-PDMA-lignin, and it is not possible to reduce filtration loss efficiently.
[0070] The present invention has been described in detail above in conjunction with specific exemplary embodiments. However, it should be understood that various modifications and variations may be made without departing from the scope of the present invention as defined by the appended claims. The detailed description should be considered only as illustrative, not restrictive, and any such modifications and variations, if any, will fall within the scope of the present invention described herein. In addition, the background art is intended to illustrate the current status and significance of the research and development of the present technology and is not intended to limit the present invention or the application field of the present application and the present invention.
[0071] More specifically, although exemplary embodiments of the present invention have been described herein, the present invention is not limited to these embodiments, but includes any and all embodiments that are recognizable by those skilled in the art based on the foregoing detailed description, such as combinations between the various embodiments, adaptive changes and / or replacements. The limitations in the claims may be interpreted broadly based on the language used in the claims and are not limited to the examples described in the foregoing detailed description or during the implementation of the application, which examples should be considered non-exclusive. Any steps listed in any method or process claim may be performed in any order and are not limited to the order presented in the claim. Therefore, the scope of the present invention should be determined solely by the attached claims and their legal equivalents, rather than by the description and examples given above.
[0072] Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those of ordinary skill in the art to which the present invention belongs. When there is a conflict, the definitions in this specification shall prevail. When flow, power, refractive index, time, or other values or parameters are expressed as ranges, preferred ranges, or a series of upper preferred values and lower preferred values, this should be understood to specifically disclose all ranges formed by any pairing of any upper range limit or preferred value with any lower range limit or preferred value, regardless of whether the range is disclosed separately. For example, a range of 1-50 is understood to include any number, combination of numbers, or subrange selected from 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, or 50, and all decimal values between the above integers, for example, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, and 1.9. With respect to subranges, "nested subranges" extending from any endpoint within the range are specifically contemplated. For example, nested sub-ranges of the exemplary range 1-50 may include 1-10, 1-20, 1-30, and 1-40 in one direction, or 50-40, 50-30, 50-20, and 50-10 in the other direction.
Claims
1. A method for preparing a polymer fluid loss reducer for drilling fluid, characterized in that: The steps include: (1) N,N-dimethylacrylamide, N,N-methylenebisacrylamide and α-ketoglutaric acid were mixed in water at a molar ratio of 1:(0.005-0.015):(0.001-0.005) and then injected into a 100×100×2 mm 3 and a rectangular mold that can transmit ultraviolet light; the rectangular mold is made of glass with an ultraviolet transmittance of ≥90%; (2) A rectangular mold containing an aqueous solution of N,N-dimethylacrylamide, N,N-methylenebisacrylamide and α-ketoglutaric acid is exposed to 200-300 W ultraviolet light for 8-16 hours, wherein the ultraviolet light is directly irradiated on a 100×100 mm area of the rectangular mold. 2 On the other hand, after the reaction is completed, the solid A-type PDMA, i.e. A-PDMA, is obtained by drying; (3) Adding N,N-dimethylacrylamide, N,N-methylenebisacrylamide, an initiator and lignin into a solvent DMF and mixing and reacting them at 40-60°C for 14-20 hours to obtain a hybrid solution of type B PDMA and lignin, namely, a B-PDMA-lignin hybrid solution; wherein the molar ratio of N,N-dimethylacrylamide, N,N-methylenebisacrylamide and the initiator is 1:(0.001-0.005):(0.0005-0.004), and the mass ratio of N,N-dimethylacrylamide and lignin is 1:(0.5-4); (4) Add the A-PDMA to the B-PDMA-lignin hybrid solution, mix and stir evenly, and incubate at room temperature for 12 to 36 hours to obtain a mixed gel of A-PDMA / B-PDMA-lignin, which is a filtrate reducer; the mass ratio of A-PDMA to B-PDMA in the B-PDMA-lignin hybrid is 1:(1.2 to 2.5).
2. The method for preparing a polymer fluid loss reducer for drilling fluid according to claim 1, characterized in that: In the step (1), 20 mL of an N,N-dimethylacrylamide aqueous solution with a concentration of 1 to 10 wt.% is prepared, N,N-methylenebisacrylamide and α-ketoglutaric acid are added to the N,N-dimethylacrylamide aqueous solution and stirred evenly, and then the stirred mixed aqueous solution is injected into the rectangular mold.
3. The method for preparing a polymer fluid loss reducer for drilling fluid according to claim 2, characterized in that: The molar ratio of the N,N-dimethylacrylamide, N,N-methylenebisacrylamide and α-ketoglutaric acid is 1:0.012:0.
004.
4. The method for preparing a polymer fluid loss reducer for drilling fluid according to claim 1, characterized in that: In the step (2), the wavelength of the ultraviolet light is 360-380 nm.
5. The method for preparing a polymer fluid loss reducer for drilling fluid according to claim 1, characterized in that: In the step (2), the product after the reaction is dried at 30-40° C. to obtain the A-PDMA.
6. The method for preparing a polymer fluid loss reducer for drilling fluid according to claim 1, characterized in that: In the step (3), lignin is first added to 30 mL of DMF solvent and stirred until completely dissolved to obtain a DMF solution of lignin with a concentration of 1 to 10 wt.%, and then N,N-dimethylacrylamide, N,N-methylenebisacrylamide and an initiator are added to the DMF solution of lignin to react.
7. The method for preparing a polymer fluid loss reducer for drilling fluid according to claim 6, characterized in that: The initiator includes one or more of azobisisobutyronitrile, azobiscyclohexanecarbonitrile and benzoyl peroxide.
8. A polymer fluid loss reducer for drilling fluid, characterized in that: The method is prepared according to any one of claims 1 to 7.
Citation Information
Patent Citations
Method for preparing high-strength lignin hydrogel with adjustable mechanical properties
CN110092921A
Lignin-based temperature-resistant salt-resistant adhesion water plugging gel as well as preparation method and application thereof
CN118599071A